Energetic topography in adsorption onto heterogeneous surfaces - Ramirez Pastor, Antonio Jose (2007)
The adsorption of gases onto heterogeneous surfaces has been reviewed, highlighting models capable of taking energetic topography effects into account. The basic ideas are contained in the fundamental Generalized Gaussian Model (GGM) developed to represent mobile adsorption onto heterogeneous surfaces at low coverage, where the energetic topography is considered through an adsorptive energy distribution with a spatial correlation function. Adsorbate molecules interact amongst them via Lennard-Jones interactions. Model predictions have been compared to Monte Carlo simulations of adsorption onto heterogeneous solids obtained by doping a pure crystalline solid with different concentrations of impurities. Energetic topography effects were shown to be important, being predicted correctly by the model at low coverage. In addition, a simplified patchwise model was also considered. The adsorption of particles with nearest-neighbour attractive and repulsive interactions was studied using Monte Carlo simulation on bivariant surfaces characterized by patches of weak and strong adsorbing sites of size "i". Patches were considered to have either a square or a strip geometry, arranged either in a deterministic ordered structure or in a random way. Quantities have been identified which scale obeying power laws as a function of the scale length "l". The consequences of this finding for the determination of the energetic topography of a surface from adsorption measurements were discussed.